Validation of a Turkish version of the interpersonal outcome expectancies for thinness (IOET) scale in university students - Alim, Nural Erzurum; Çaliskan, Gözde; Gokustun, Kerim Kaan; Akkus, Zebra Nur (MATTIOLI 1885, 2019)
Aim: The aim of this study was to determine the validity and reliability of IOET in Turkish university students. Methods: First, the IOET scale was translated by using the translation-back translation method for cultural equivalence. Then, IOET was carried out on 513 university students explanatory and confirmatory factor analyzes. The body shape questionnaire and the Nutritional Changes Processes Scale were used for convergent validity. Test-retest validity was performed with 117 university students 4 weeks after the scale was given. Results and Discussion: The IOET scale showed a one-factor structure. The one-factor structure of the scale demonstrated a good agreement with the fix index values. In addition, the internal and test-retest validity reliability of the scale was found to be good (Cronbach alpha= 0.933). Positive, statistically significant correlations were found between IOET, the body shape questionnaire, and the Nutritional Changes Processes Scale (p < 0.05). This study has shown that the Turkish version of the IOET scale is a valid and reliable instrument for assessing the extent to which thinness can affect interpersonal relationships and/or our expectations from the other people. It is thought that IOET-TR can contribute to other studies on thinness expectations by providing a different perspective.
Keywords: Body image; eating disorders; thinness expectancies; IOET; validity; reliability